2015
DOI: 10.1590/1982-0224-20140165
|View full text |Cite
|
Sign up to set email alerts
|

Feeding and reproductive ecology of Cichla piquiti Kullander & Ferreira, 2006 within its native range, Lajeado reservoir, rio Tocantins basin

Abstract: Cichla piquiti is endemic to the Tocantins-Araguaia river basin, but information about its biology is restricted to populations introduced in other basins. In order to fill this gap, we investigated the feeding ecology and reproductive dynamics of C. piquiti in Lajeado reservoir, rio Tocantins. A total of 270 fish were collected between November 2010 and October 2011. The diet is rich and composed of at least 23 resources, predominantly fish (at least 19 species). We observed no clear influence of sex, periods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
0
3
0
3
Order By: Relevance
“…The observation of mature males and females during most of the year seems to be a general consensus for nonnative Cichla populations in altered environments in Brazil (Chellapa et al, 2003;Gomiero & Braga, 2004a;Gomiero et al, 2009;Vieira et al 2009;Normando et al 2009;Luiz et al, 2011;Souza et al, 2008), the United States (Shafland, 1999) and Panama (Zaret, 1980). A similar pattern was also reported for populations in native ranges of distribution (but impacted by dams), as in the cases of Cichla piquiti Kullander & Ferreira, 2006, in the Lajeado Reservoir (Tocantins-Araguaia River basin;Marto et al, 2015) and Cichla vazzoleri Kullander & Ferreira, 2006, in the Balbina Reservoir (Central Amazon;Horie, 2013). Although these studies in altered environments indicate that reproduction can potentially occur over a long period, reproductive peaks vary considerably within and between populations, at times and under contrasting environmental conditions.…”
Section: Regenerationmentioning
confidence: 56%
See 2 more Smart Citations
“…The observation of mature males and females during most of the year seems to be a general consensus for nonnative Cichla populations in altered environments in Brazil (Chellapa et al, 2003;Gomiero & Braga, 2004a;Gomiero et al, 2009;Vieira et al 2009;Normando et al 2009;Luiz et al, 2011;Souza et al, 2008), the United States (Shafland, 1999) and Panama (Zaret, 1980). A similar pattern was also reported for populations in native ranges of distribution (but impacted by dams), as in the cases of Cichla piquiti Kullander & Ferreira, 2006, in the Lajeado Reservoir (Tocantins-Araguaia River basin;Marto et al, 2015) and Cichla vazzoleri Kullander & Ferreira, 2006, in the Balbina Reservoir (Central Amazon;Horie, 2013). Although these studies in altered environments indicate that reproduction can potentially occur over a long period, reproductive peaks vary considerably within and between populations, at times and under contrasting environmental conditions.…”
Section: Regenerationmentioning
confidence: 56%
“…Franco et al (2018) reported that increased reservoir water retention time, when combined with warmer and more transparent waters, can increase the abundance of peacock bass. The advantage of the strategy of equilibrium in altered environments may be associated to the fact that the lentic conditions and greater hydrological stability of the reservoirs promote adequate conditions for nest building and protection of juveniles (Marto et al, 2015;Muñoz et al, 2006;Winemiller, 2001). Consequently, the strategy of equilibrium and plasticity in reproductive traits may be the main factors inherent in the successful colonization and settlement of the peacock bass in the environments in which the species were introduced.…”
Section: Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…As populações de C. piquiti, espécie nativa da bacia hidrográfica do Tocantins-Araguaia, foram avaliadas em reservatórios situados em diferentes latitudes e, consequentemente, diferentes características ambientais e climáticas. Os estudos foram realizados em Tocantins (Marto et al, 2015), São Paulo (Franceschini et al, 2013)…”
Section: Proporção Sexualunclassified
“…Em sua área de distribuição natural (Muñoz et al, 2006), os machos apresentaram peso total superior de duas vezes a três vezes mais elevada que aquelas determinadas nos ambientes onde o tucunaré foi introduzido. O valor de massa corporal mais alto obtido neste estudo foi observado na população de C. piquiti investigada por Marto et al (2015), sendo igual a 3,3kg. Além disso, também foi o segundo maior valor em comprimento, menor apenas que os 55cm relatados para a espécie C. monoculus na Amazônia (Muñoz et al, 2006).…”
Section: Estrutura Populacional Em Comprimento E Pesounclassified